PENINGKATAN PENGETAHUAN MENGENAI BENCANA GEMPABUMI MELALUI PERMAINAN SOS DAN PUZZLE DI SMP NEGERI 1 POLANHARJO KABUPATEN KLATEN - Dewi, Ratih Puspita; Musiyam, Muhammad; Wibowo, Yunus Aris; Pambudi, Wulansari Dwi; Santoso, Dimas (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
An earthquake is a type of natural disaster which occurs due to the movement of tectonic plates. The time and location of an earthquake cannot be predicted, so people living in earthquake-prone areas should have good knowledge of earthquake disasters as capital in anticipating earthquake disasters. Various efforts need to be made to increase knowledge about earthquake disasters, one of which is through education. In the education sector, efforts to increase knowledge about earthquake disasters can be done through the integration of game-based learning in schools. One of the schools that is vulnerable to earthquakes is SMP Negeri 1 Polanharjo, Klaten Regency. This school is one of the schools that was affected by the earthquake disaster in Klaten Regency in 2006. The aim of this activity is to (1) increase knowledge about earthquake disasters through the implementation of game-based learning media (disaster SOS and puzzles) for social studies teachers and students at SMP Negeri 1 Polanharjo and (2) increase the capacity of teachers and students in dealing with earthquake disasters. The targets of this activity are social studies teachers and OSIS administrators at SMP Negeri 1 Polanharjo. The implementation method is through socialization and practice in using game-based learning media, namely disaster SOS and puzzles. The results of the activity showed that (1) the implementation of game-based learning media (disaster SOS and puzzles) can increase the motivation of teachers and students in studying earthquake disasters and (2) this media can increase the capacity of teachers and students regarding earthquake disasters.